The Effect of Google Classroom Assisted Extensive Listening on Listening Comprehension Accross Learning Autonomy - Melyann Melani (Lingua Cultura, 2020)
The research aimed at identifying the effect of Google Classroom Assisted Extensive Listening (EL) on English as a Foreign Language (EFL) Students’ Listening Comprehension across Learning Autonomy (i.e., high learning autonomy, and low learning autonomy). The research involved 78 students from two classes, which were divided into the experiment and control group. The experiment class was treated by practicing EL with the support of Google Classroom, on the other hand, the control group was treated by practicing EL by using the traditional platform (written listening journal). The students in each group were further grouped based on their autonomy level (high and low). The result of the research reveals that the mean score of the experiment group is much higher than the control class. It means that students who practiced EL with the support of Google Classroom have better listening comprehension as compared to the students who practiced EL by using the traditional platform. However, the research indicates no interaction from each learning autonomy level with the listening comprehension of both groups.